Validating measurement techniques during accreditation of testing laboratory validating - Володарский, Евгений Тимофеевич; Кошевая, Лариса Александровна (Technology audit and production reserves, 2014)
The procedure of validating measurement techniques, which is necessary during accreditation of testing laboratories, is described in the paper. Today, the validation procedure in most cases does not have a regulatory-methodological support. The peculiarity of its conducting in different situations, which occur in practical activities of testing laboratories, is shown. The examples of calculating validation characteristics, the choice of which depends on the type of a measurement technique, its modification extent, alteration of intermediate precision factors, have been presented. It is shown that the necessary condition for validating a certificated technique is the confirmation of acceptability of results using statistical criteria. The association between statistical accuracy indicators of a technique and measurement uncertainty has been considered. It is shown that random factors are estimated by repeatability, equipment influence, calibration, conditions, operator, i.e. reproducibility, while factors, unaccounted by these characteristics, are estimated by uncertainty of results.